QUR’ANIC PERSPECTIVES ON CARING FOR THE ELDERLY - Thaib, Zamakhsyari Hasballah (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2021)
Abstract: This article aims to describe the amount of attention that the Qur’ân has given to the problems of caring for the elderly. The author examined this topic using thematic interpretation methods by collecting âyahs that are closely related to keywords in the study, according to the induction (istiqrâ') method. Among the main conclusions in this paper, there were many words used in the Qur'ân which refer meaning of elderly such as al-kibar, ‘ajûz, syeikh, arzal al-‘umr, wahana al-‘azhm, dha‘f, and syaibah and their derivations. Al-Qur’ân suggests that old age is an extended period; there are ordinary elderly and late elderly, each has different characteristics. In caring for the elderly, several Qur’ânic principles should always be considered, among them; glorifying and honouring the elderly is one of the main characteristics of Islamic society. It is hoped that through these qur’ânic principles, care and respect for the elderly will be better among the Muslim community, especially in Indonesia.Keywords: elderly, Qur’ânic principles, Qur’ânic exegesis